Proactive Monitoring of Chronic Conditions Using WMDs in Primary Care: Protocol of a Multicentre Feasibility Randomized Controlled Trial Across Italy and Finland - Mezzalira, Elisabetta; Saiani, Luisa; Axelin, Anna (Milano University Press, 2026)
BACKGROUND: Wearable monitoring devices (WMDs) have emerged as a promising tool for supporting self-management of chronic conditions, but sustained long-term use remains a challenge. This multicentre feasibility randomized controlled trial aims to develop and evaluate a proactive monitoring intervention utilizing WMDs for individuals with chronic conditions in primary care settings across Italy and Finland.
METHODS: The intervention will be developed following the Medical Research Council framework, guided by the Self-Determination Theory. Focus groups with stakeholders will inform the design of the intervention procedures, training materials, and strategies to promote sustained WMD use by facilitating competence, autonomy, and relatedness. The feasibility trial will randomize participants to either the WMD intervention group, receiving proactive monitoring by family and community nurses, or a control group receiving standard care. Outcomes include usability, feasibility (recruitment, attrition, technical difficulties), implementation (continued use, adherence), quality of life, self-efficacy, and health service utilization. Qualitative data will explore cultural differences between the two countries.
RESULTS AND CONCLUSION: By prioritizing stakeholder engagement, theoretical grounding, and pragmatic considerations during the intervention development phase, this study aims to develop a feasible and effective proactive monitoring program to enhance chronic condition management through sustained WMD use in primary care across different European contexts, enhancing the opportunities for nurses to have advanced tools for patient monitoring and self-efficacy strategies.